Comparative study on structural characterization, physicochemical properties, and in vitro probiotic activities of resistant starch from different varieties of Euryale ferox - Cheng Qu; Daixin Yu; Zonghui Jing; Shuyu Gu; Yufei Wang; Weifan Xie; Qinan Wu (Food Chemistry: X)
Euryale ferox (EF), a highly nutritious food, is an excellent source of resistant starch (RS). This study compared the structure, physicochemical properties, and probiotic activities of RS from North (NEFRS) and South EF (SEFRS). NEFRS exhibited a higher RS content (∼10 %) than SEFRS (∼4 %) and demonstrated superior crystallinity (21.66 %), thermal stability (ΔH = 21.85 J/g), and molecular order, whereas SEFRS contained more double helices (ΔH = 4.17 J/g). Both displayed type A crystalline structures, with RS5 amylose–lipid complexes being more abundant in NEFRS during growth. Gas chromatography–mass spectrometry identified bound fatty acids, including palmitic, linoleic, trans-oleic, and stearic acids, confirmed through in vitro synthesis. Probiotic assays revealed EFRS enhanced the growth of Bifidobacterium and Lactobacillus acidophilus, while NEFRS exhibited stronger inhibition against Escherichia coli and Staphylococcus aureus. Overall, this study systematically elucidated the EFRS differences between two species, providing valuable insights into functional product development and EF deep processing.